SPS155 : Professional activity (swimming and golf) / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2020)
This course will introduce students to various techniques of swimming. Topics covered will include general knowledge, learning and coaching progression, training, planning and organization of swimming programme and practical experience.